Implementing community level water management in coastal Bangladesh – a case study in polder 30, CPWF Innovation Funds Project Completion Report - CGIAR Challenge Program on Water and Food (2014)
The goal of this Innovation Grant project was: To work with the community in a pilot “watershed” area to demonstrate the potential crop production benefits through improved management of water in the polders of the coastal zone of Bangladesh, and to demonstrate how to achieve these benefits.